2009
DOI: 10.1093/cvr/cvp414
|View full text |Cite
|
Sign up to set email alerts
|

Decreased rates of substrate oxidation ex vivo predict the onset of heart failure and contractile dysfunction in rats with pressure overload

Abstract: Pressure overload-induced impairment in fatty acid oxidation precedes the onset of congestive heart failure but mitochondrial respiratory capacity is maintained until the EF decreases in vivo. These temporal relations suggest a tight link between impaired substrate oxidation capacity in the development of heart failure and contractile dysfunction and may imply therapeutic and prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
171
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(192 citation statements)
references
References 43 publications
13
171
0
8
Order By: Relevance
“…This is in line with what has been shown in children with right ventricular failure secondary to congenital heart disease48 and in mice with myocardial remodeling and failure postinfarction 49. It has been shown that PGC‐1α controls mitochondrial density50 and fatty acid oxidation51, 52 and its amount directly correlates with mitochondrial density, oxidative capacity,47 and the metabolic shift from fatty acid oxidation to glucose oxidation,51 which precedes cardiac decompensation 46. Previous studies assessing changes in the expression and activity of the ETC complexes in HF have shown variable results, and such changes may vary according to the HF model 45.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with what has been shown in children with right ventricular failure secondary to congenital heart disease48 and in mice with myocardial remodeling and failure postinfarction 49. It has been shown that PGC‐1α controls mitochondrial density50 and fatty acid oxidation51, 52 and its amount directly correlates with mitochondrial density, oxidative capacity,47 and the metabolic shift from fatty acid oxidation to glucose oxidation,51 which precedes cardiac decompensation 46. Previous studies assessing changes in the expression and activity of the ETC complexes in HF have shown variable results, and such changes may vary according to the HF model 45.…”
Section: Discussionsupporting
confidence: 87%
“…This early time point following banding was chosen due to the quick decline in the survival of Chip -/-mice following the induction of pressure overload ( Figure 1B). Following 1 week of banding, total ATP levels in extracts isolated from wild-type mice increased 1.8 fold ( Figure 2D and Supplemental Table 5), consistent with recent metabolic studies demonstrating energetic adaptation to maintain cardiac power during the initial compensation to pressure overload (20,21). In contrast, total ATP levels failed to increase in extracts isolated from Chip -/-banded hearts, supporting the theory that CHIP may be involved in ATP generation during cardiac pressure overload.…”
Section: Figuresupporting
confidence: 86%
“…In a model of aortic arch constriction, Doenst et al 60 investigated cardiac function and fatty acid and glucose metabolism during the development of hypertrophy and heart failure. Diastolic and systolic dysfunction were observed at 6 weeks and 10 weeks, respectively, following aortic constriction.…”
Section: Cardiac Metabolism In Left Heart Failurementioning
confidence: 99%